Energy efficiency in data centers and clouds - Hurson, Ali; Sarbazi-Azad, Hamid; ScienceDirect eBooks (Cambridge, MA : Academic Press is an imprint of Elsevier, 2016)
Advances in Computers carries on a tradition of excellence, presenting detailed coverage of innovations in computer hardware, software, theory, design, and applications. The book provides contributors with a medium in which they can explore their subjects in greater depth and breadth than journal articles typically allow. The articles included in this book will become standard references, with lasting value in this rapidly expanding field.
Power management in data centers: cost, sustainability, and demand response / Thant Zin Oo, Nguyen H. Tran, Choong Seon Hong, Shaolei Ren, Gang Quan -- Energy-efficient big data analytics in datacenters / Farhad Mehdipour, Hamid Noori, Bahman Javadi -- Energy-efficient and SLA-based resource management in cloud data centers / Altino M. Sampaio, Jorge G. Barbosa -- Achieving energy efficiency in datacenters by virtual machine sizing, replication, and placement / Hadi Goudarzi, Massoud Pedram -- Communication-awareness for energy-efficiency in datacenters / Seyed Morteza Nabavinejad, Maziar Goudarzi.
Print version record.
Includes bibliographical references and indexes.
Elsevier
Keywords: Data libraries -- Energy consumption; COMPUTERS / Computer Literacy; COMPUTERS / Computer Science; COMPUTERS / Data Processing; COMPUTERS / Hardware / General; COMPUTERS / Information Technology; COMPUTERS / Machine Theory; COMPUTERS / Reference; Electronic books